(untitled) (Iraqi Journal of Medical Sciences, 2019)
Background:Atopic dermatitis (AD) is a common inflammatory skin disease with a chronic relapsed-remitting course with manifestations started at early childhood. AD is two types; extrinsic and intrinsic. Zinc has a crucial role in the immune system functions and antioxidant mechanisms, it also serves in the metabolism and cell growth through signaling several enzymes. Objective:To assess serum zinc level in patients with childhood AD. Methods:A case-controlled study was conducted in Dermatology outpatient’s clinic in Al-Imamein Al-Kadhimein Medical City, from the period of September 2016- June 2017. Twenty patients with AD were enrolled in this study. AD severity was graded using the Scoring Atopic Dermatitis Index (SCORAD). The control group consisted of age-matched and sex-matched twenty healthy children were taken with weight above 80%. Fasting blood samples were taken from patients and controls between 8 AM and 10 AM. Results:Of the twenty patients of AD, 13 (65%) were males and 7 (35%) were females. Their mean age was 4.58±3.13. Regarding the control group 9 (45%) were males and 11 (55%) were females, their mean age was 4.29±2.46. No statistical difference in serum zinc level between AD patients and control groups. Concerning zinc level in males and females, no statistical differences was found in AD patients, but highly significant difference was found in control group. Serum zinc level was highly significantly low in patients with moderate AD than in those with mild AD. There was negative correlation between serum zinc level and severity of AD. Conclusion:There is a negative correlation between serum zinc level and severity of AD, also there is a gender variation in serum zinc level in normal children. Keywords:Serum zinc level, atopic dermatitis Citation: Farhood IG, Ahmed MA, Al-Bandar RT, Farhood RG. Assessment of serum zinc level in patients with atopic dermatitis. Iraqi JMS. 2019; 17(2): 103-107. doi: 10.22578/IJMS.17.2.2